2007
DOI: 10.1152/ajpheart.00993.2006
|View full text |Cite
|
Sign up to set email alerts
|

Medroxyprogesterone acetate prevents the cardioprotective and anti-inflammatory effects of 17β-estradiol in an in vivo model of myocardial ischemia and reperfusion

Abstract: Booth EA, Lucchesi BR. Medroxyprogesterone acetate prevents the cardioprotective and anti-inflammatory effects of 17␤-estradiol in an in vivo model of myocardial ischemia and reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…In addition to the increasing number of incidents with oxidative damage and inflammatory processes, enhanced programmed cell death in IBH was also exhibited in the literature [9][10][11] . Programmed cell death is defined as apoptosis.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition to the increasing number of incidents with oxidative damage and inflammatory processes, enhanced programmed cell death in IBH was also exhibited in the literature [9][10][11] . Programmed cell death is defined as apoptosis.…”
Section: Discussionmentioning
confidence: 91%
“…The sections were examined for the presence of edema, necrosis, inflammatory infiltration, apoptosis, vascular congestion and thrombosis and severity and prevalence of partial separation in apical epithelial cells. The histopathologist was blinded for group allocation and performed all analyses and graded microscopic changes in the colonic mucosa from 0 to 3 9,10 .…”
Section: Macroscopic Scoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Infarct size is of pivotal importance for the extent of cardiac remodeling and chronic HF following MI. Booth and Lucchesi (2007) and Jeanes et al (2006) previously reported that an acute addition of MPA to an E2 treatment resulted in an extension of the necrotic zone after a cardiac ischemic effect. Nonetheless, those findings were limited to the events occurring during the first 4 hours after reperfusion injury.…”
Section: Discussionmentioning
confidence: 98%
“…For example, MPA attenuates the beneficial effects of estrogens on endothelial-dependent relaxation and release of NO (antimitogenic molecule), 10,17,18 increases vascular procoagulant activity by upregulating thrombin receptor PAR-1 expression, 15 abrogates the cardioprotective and anti-inflammatory effects of estradiol, 19 attenuates the favorable effects of orally administered estrogens on high-density lipoprotein, 9 and abrogates the inhibitory effects of estradiol on injury-induced neointima formation. 12 Finally, although the above findings suggest that MPA can abrogate the protective effects of estradiol, it should be noted that the estrogen alone arm of the Women's Health Initiative Study did not show positive results, suggesting that factors other than MPA may also contribute to the lack of cardiovascular protective actions by estrogens in the Women's Health Initiative Study.…”
Section: Discussionmentioning
confidence: 99%